Juvenile confinement exacerbates adversity burden: A neurobiological impetus for decarceration - Orendain, Natalia; Galván, Adriana; Smith, Emma; Barnert, Elizabeth S.; Chung, Paul J. (Frontiers in Neuroscience, 2022)
Every year, about 700,000 youth arrests occur in the United States, creating significant neurodevelopmental strain; this is especially concerning as most of these youth have early life adversity exposures that may alter brain development. Males, Black and Latinx youth, and individuals from low socioeconomic status households have disproportionate contact with the juvenile justice system. Youth confined in the juvenile justice system are frequently exposed to threat and abuse, in addition to separation from family and other social supports. Youths’ educational and exploratory behaviors and activities are substantially restricted, and youth are confined to sterile environments that often lack sufficient enrichment resources. In addition to their demonstrated ineffectiveness in preventing future delinquent behaviors, high recidivism rates, and costs, juvenile conditions of confinement likely exacerbate youths’ adversity burden and neurodevelopmentally harm youth during the temporally sensitive window of adolescence. Developmentally appropriate methods that capitalize on adolescents’ unique rehabilitative potential should be instated through interventions that minimize confinement. Such changes would require joint advocacy from the pediatric and behavioral health care communities.